2022
DOI: 10.33448/rsd-v11i10.31750
|View full text |Cite
|
Sign up to set email alerts
|

The role of phenolic compounds in metabolism and their antioxidant potential

Abstract: The intake of fruits and vegetables rich in nutrients with bioactive properties is associated with the prevention of a range of chronic diseases such as cardiovascular diseases, diabetes, and cancer that originate from physiological disorders, which can be promoted by the accumulation of free radicals in the body. Several chemical compounds with bioactive functions are found in fruits and vegetables. Among these, phenolic compounds stand out for having high antioxidant capacity. These compounds originate from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
1
0
0
Order By: Relevance
“…The Fraction F and compound (6) were able to protect viable epidermis against UVAinduced ROS production, with a reduction of 34.6% and 30.2% in the uorescence, respectively, both when tested at 10.0 µg/mL. As mentioned, this antioxidant activity can be due to the presence of polyphenolic compounds capable of neutralizing free radicals and other ROS(Souza et al, 2019, Silva et al, 2022, which is in agreement with the protection observed in HaCaT keratinocytes.…”
supporting
confidence: 84%
“…The Fraction F and compound (6) were able to protect viable epidermis against UVAinduced ROS production, with a reduction of 34.6% and 30.2% in the uorescence, respectively, both when tested at 10.0 µg/mL. As mentioned, this antioxidant activity can be due to the presence of polyphenolic compounds capable of neutralizing free radicals and other ROS(Souza et al, 2019, Silva et al, 2022, which is in agreement with the protection observed in HaCaT keratinocytes.…”
supporting
confidence: 84%